PHOTOCATALYTIC DEGRADATION OF BATIK DYE EFFLUENTS USING ZINC OXIDE (ZNO) NANORODS SYNTHESIZED VIA A GREEN CHEMISTRY APPROACH - Nurul Huda; Sharmin Sultana; Dineo Mabuza (Research of Scientia Naturalis, 2025)
The discharge of batik dye effluents into water bodies is a significant environmental concern, as it contains toxic azo dyes that are difficult to degrade. Traditional methods for dye removal, such as chemical oxidation and adsorption, often have limitations in terms of cost, efficiency, and environmental impact. This study aims to investigate the photocatalytic degradation of batik dye effluents using zinc oxide (ZnO) nanorods synthesized through a green chemistry approach. ZnO nanorods were synthesized using natural plant extracts as reducing agents, offering an environmentally friendly and cost-effective alternative to conventional methods. The photocatalytic performance of the synthesized ZnO nanorods was evaluated by exposing them to batik dye effluents under UV light. The effects of parameters such as pH, catalyst dosage, and UV exposure time were studied. The results showed that ZnO nanorods exhibited significant degradation of the dye, with optimal performance achieved at pH 5, a catalyst dosage of 0.2 g, and 120 minutes of UV exposure. The nanorods demonstrated high reusability, making them suitable for long-term application in wastewater treatment. This study highlights the potential of ZnO nanorods synthesized via green chemistry as an efficient, eco-friendly solution for treating batik dye effluents, offering a sustainable alternative to traditional wastewater treatment methods.